Cast insertions of the tram current collector from aluminium discard - A. A. Andrashevich; I. N. Kazanevskaja; M. N. Churik (Литьë и металлургия)
In the article there are given the results of investigations and developments of the production technology of slugs of the tram current collectors insertions from aluminium waste by casting method in iron chill with running ability at level of insertions, received by hot pressing.